Development and performance evaluation of a car brake bleeding tool to reduce labor and service time at PT. UMC Suzuki Ahmad Yani Surabaya - Raihan Ramadhani; M. Khaniful Annas; Yoga Guntur Sampurno (Universitas Negeri Yogyakarta, 2025)
The objectives of this research are: (1) Designing a brake bleeding tool that will be used for the process of bleeding car brakes at the UMC Suzuki Ahmad Yani Surabaya workshop, (2) Knowing the effectiveness of the brake bleeding tool when used at the UMC Suzuki Ahmad Yani Surabaya workshop, (3) Finding out work efficiency after work is carried out using the brake bleeding tool at the UMC Suzuki Ahmad Yani Surabaya workshop. The design of the car brake bleeding tool was developed through analysis, design, development, implementation, and evaluation, resulting in a specialized tool that enhances the mechanic's work at the PT UMC Suzuki Ahmad Yani Surabaya workshop. This tool helps mechanics bleed car brakes, which previously required conventional tools and at least 2-3 additional mechanics. With the developed brake bleeding tool, mechanics only need to work with one person. This tool can also reduce the time required for brake bleeding, which is usually 17 minutes, to just 9 minutes. The development of a brake bleeding tool proved very effective in expediting brake bleeding maintenance at the UMC Suzuki Ahmad Yani Surabaya workshop. With this tool, manual bleeding tools are no longer required, making work more effective without additional labor. This tool produces a time efficiency of 55%. This tool makes the brake bleeding process more accurate and reliable, providing consistent quality assurance and, overall, increasing the productivity and effectiveness of workshop operations.